MA’ SULANG (PENEBUSAN TANAH GADAI ADAT) MASYARAKAT TANA TORAJA DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Rombeallo, Yulianus M; Gela M.S, Bergita; Rante, Marchelina (UNES Law Review, 2023)
In traditional pawning in Tana Toraja, redemption of the pawned land is known as Ma'Sulang. Where the party who redeems the land has the right to get the land. However, in the context of Indonesian written law, this has not been accommodated in a written statutory regulation so that it could lead to different interpretations by the parties involved in the process of pawning the customary land, giving rise to legal uncertainty. The method in this research is empiricial that examinethe applicable legal provisions and what happens in reality in society. The results of the study confirm the difference between ma' sulang and the written legal provisions in Article 7 of Perpu No. 56 of 1960 concerning Determination of Agricultural Land Areas for redemption of pawns contains rules for a time limit of 7 years and the recipient of the pawn is obliged to return the pawned land to its owner with no right to demand a ransom payment, while the rules for redeeming traditional pawns (ma' sulang) do not recognize a time limit. but the obligation to return is binding. The lender is obliged to redeem his land if he wants the land back. The object of land from Ma' Sulang can also be applied for the issuance of a certificate of ownership of land rights while still adhering to the written legal provisions. making a letter of approval for the distribution of inheritancesigned by other heirs in the presence of witnesses and authorized officials.